Legal Responsibility of Military Doctors in Indonesia: A Study of Military and Health Law - I Komang Tresna; Francis Maryane Pattynama; Ahmad Heru Romadhon (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2026)
This study aims to analyze the legal responsibility of military doctors in malpractice cases from the perspectives of health law and military criminal law in Indonesia. Military doctors hold a dual status as members of the Indonesian National Armed Forces (TNI) and as professional medical practitioners, thereby subjecting them to two legal regimes simultaneously. This research employs an empirical method with a statutory approach, supported by primary and secondary legal materials. The results show that from the perspective of health law, legal responsibility is based on the existence of professional fault, proven through violations of professional standards, standard operating procedures, and medical service standards, with forms of liability including ethical, administrative, civil, and criminal aspects. From the perspective of military criminal law, responsibility emphasizes discipline, command hierarchy, and organizational interests, with possible sanctions in the form of criminal penalties and military administrative sanctions. The determination of judicial forum is principally under the jurisdiction of Military Courts based on the principle of personality. However, if the case involves both military and civilian actors, the mechanism of connectivity courts applies to ensure unity of examination and legal certainty. Civil disputes remain under the jurisdiction of general courts and are preceded by professional disciplinary mechanisms through the Indonesian Medical Discipline Honor Council (MKDKI). Thus, the legal responsibility of military doctors in malpractice cases reflects an integration between health law and military criminal law in ensuring legal certainty and justice.